A feasible self-assembled near-infrared fluorescence sensor for acid phosphatase detection and cell imaging. Issue 18 (16th August 2021) - Li, Shuangqin; Wang, Yaya; Mu, Shuai; Zhang, Jinlong; Liu, Xiaoyan; Rizvi, Syed Faheem Askari; Zhang, Haixia; Ding, Nana; Wu, Lan
Abstract : A feasible self-assembly near-infrared fluorescence sensor for acid phosphatase detection and cell image. Abstract : The single signal amplification strategy is significant for detecting various disease biomarkers but is restricted by its limited accuracy. The multi-signal and multi-mode methods have overcome this deficiency. Acid phosphatase (ACP) is an important intracellular enzyme but one-step cell imaging material-based probes are scarce for ACP. Herein, we designed a one-step self-assembled polymer probe using neutral red (NR), modified-(pyridoxal-5′-phosphate (PLP)) and Eu 3+ . The polymer exhibited non-emission and excellent stability. Upon the catalytic hydrolysis reaction of ACP, the polymer exhibited two strong fluorescence signals at 373 nm and 613 nm and an appreciable decline of absorbance at 395 nm. The probe has excellent selectivity and higher sensitivity with a limit of detection as low as 0.02 mU mL −1 . It possesses favorable biocompatibility and has been successfully used to detect and image intracellular ACP in several living cells.